PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DESA GERNIS JAYA KECAMATAN SEPAUK KABUPATEN SINTANG - S.S, Antonius (Universitas Kapuas Sintang, 2025)
Development planning is a systematic effort by various actors, both private government and other community groups at different levels. The performance of the existing development in Gernis Jaya Village, Sepauk District, is considered not to be in accordance with what the community expects in carrying out comprehensive physical development. This can be seen from the less than optimal performance of the Gernis Jaya village head in preparing a work program to improve the infrastructure of Gernis Jaya Village, the development carried out by the village head was only partial so it was uneven, and the low capacity of the village head so that development did not go according to plan. The implementation of physical development by the Gernis Jaya village head has not gone well. This is proven by the existence of obstacles experienced by the village head, namely the lack of budget to carry out development, the low competence of the village head so that the development process is not going well and the low level of community awareness to build the village together in mutual cooperation. The efforts that have been made to overcome these obstacles, namely making a budget proposal plan to carry out development in stages, conducting evaluations of the performance of the village head and holding counseling or socialization related to development carried out by the village head to the community, therefore that The process of implementing physical development by the village head can run if it is supported by all important elements such as government officials and the community. With the efforts made by the village head, the obstacles that occur to physical development can be minimized.